2016
DOI: 10.1007/s00167-016-4066-5
|View full text |Cite
|
Sign up to set email alerts
|

Proximal tibiofibular joint pain versus peroneal nerve dysfunction: clinical results of closed-wedge high tibial osteotomy performed with proximal tibiofibular joint disruption

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The original goal of HTO was to correct deformities of the coronal plane, but unexpected events, the changes in the PTS, occurring in the sagittal position are always inevitable [53, 54]. Our results showed that PTS increases after OWHTO ( p < 0.05) and decreases ( p > 0.05) after CWHTO, which is consistent with several comparative studies [16, 18, 23, 24, 26].…”
Section: Discussionsupporting
confidence: 91%
“…The original goal of HTO was to correct deformities of the coronal plane, but unexpected events, the changes in the PTS, occurring in the sagittal position are always inevitable [53, 54]. Our results showed that PTS increases after OWHTO ( p < 0.05) and decreases ( p > 0.05) after CWHTO, which is consistent with several comparative studies [16, 18, 23, 24, 26].…”
Section: Discussionsupporting
confidence: 91%
“…Emerging clinical and epidemiological evidence suggests proximal tibiofibular osteoarthritis may represent an underappreciated cause of posterior and lateral knee pain [8] . For example, patients with presumed peroneal nerve dysfunction have been later found to suffer from tibiofibular articular pathology [10] . While patients with proximal tibiofemoral osteoarthritis classically present with lateral knee pain, studies have correlated posterior knee pain with imaging consistent with the disease [11] .…”
Section: Discussionmentioning
confidence: 99%
“…One of the major perioperative complications after fibular head osteotomy (FHO) is peroneal nerve disfunction. The reported incidence of symptomatic injury stands at between 3-20% [8]. On the other hand, since lateral collateral ligament (LCL) and popliteus-fibular ligament (PFL) originate on the fibular head, TFJD may lead to fibular head rise and a shift in ligament tensioning with a potential impact on lateral knee laxity [9].…”
Section: Introductionmentioning
confidence: 99%